Managing hyperglycaemia in people with DM and CKD: cardiovascular disease (CVD) involvement - Winocour, Peter (Henry Stewart Talks, 2020)
The need to individualise glycaemic control in DKD, The role of new agents in reducing development and progression of DKD, The need for co-ordinated DM care in haemodialysis, Logical and inappropriate combination blood glucose lowering therapies in DKD, Safe management of DKD during acute illness